164k views
5 votes
Given f(x)=4x and g(x) = -3x-7,evaluate (f-g) (x) at x = -3

User Limor
by
5.3k points

2 Answers

6 votes

Answer:

(f-g)(-3) = -14

Explanation:

We have given two functions and we have to find their difference.

f(x) = 4x and g(x) = -3x-7

(f-g)(x) = ? and (f-g)(-3) = ?

The formula to find the difference of two functions is:

(f-g)(x) = f(x)-g(x)

Putting the given values in above formula, we have

(f-g)(x) = 4x-(-3x-7)

(f-g)(x) = 4x+3x+7

(f-g)(x) = 7x+7

Putting x = -3 in above formula,we have

(f-g)(-3) =7(-3)+7

(f-g)(-3) = -21+7

(f-g)(-3) = -14 which is the answer.


User Oyarzun
by
6.2k points
3 votes

Answer:

(f - g)(-3) = -14

Explanation:


(f-g)(x)=f(x)-g(x)

We have


f(x)=4x,\ g(x)=-3x-7

Substitute:


(f-g)(x)=4x-(-3x-7)=4x-(-3x)-(-7)=4x+3x+7=7x+7

For x = -3.

Put the value of x to the equation of the function:


(f-g)(-3)=7(-3)+7=-21+7=-14

User TBogdan
by
5.4k points